Comparison of The Physical Fitness Parameters of Special Education Vocational School Students and Inclusion High School Students - Han, Mustafa; Akaydin, Şevval; Yilmaz, Atike; Koç, Serdar (Nevzat Demirci, 2024)
This study compared the physical fitness parameters of intellectually disabled special education vocational school students with those of inclusive high school students using the causal comparison method. Participants consisted of 22 (15 male, 7 female) from Special Education Vocational School and 25 (20 male, 5 female) inclusion students receiving inclusive education at high school. A physical fitness form was used to collect data on body mass index (BMI), standing long jump, flexibility, right-hand reaction, left-hand reaction, leg strength, back strength, right-hand grip, left-hand grip, 30 m sprint, and push-ups. The T-test was applied to data exhibiting normal distribution, while the Mann-Whitney U test was used for data not normally distributed. Among the parameters showing normal distribution, there were significant differences between the two different student groups in the standing long jump, flexibility, left-hand reaction, leg strength, and right-left hand grip strength. Although a significant difference was observed in the right-hand reaction, no significant differences were detected for the other non-normally distributed parameters of BMI, back strength, 30-m sprint, and push-ups. Our results indicated that students with intellectual disability (ID) enrolled in inclusive education at the high school level performed better in all physical fitness tests conducted compared to their peers in special education vocational schools. © 2024 Nevzat Demirci. All rights reserved.
Keywords: Inclusive Education; Intellectual Disability; Physical Fitness; Special Education Vocational School; Students With Special Needs